2018
DOI: 10.3389/fmicb.2018.00406
|View full text |Cite
|
Sign up to set email alerts
|

An Ontology Systems Approach on Human Brain Expression and Metaproteomics

Abstract: Research in the last decade has shown growing evidence of the gut microbiota influence on brain physiology. While many mechanisms of this influence have been proposed in animal models, most studies in humans are the result of a pathology–dysbiosis association and very few have related the presence of certain taxa with brain substructures or molecular pathways. In this paper, we associated the functional ontologies in the differential expression of brain substructures from the Allen Brain Atlas database, with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Following an innovative approach, Flores Saiffe Farías et al performed an in-silico framework to associate metaproteins with the brain proteins expression through ontological labels. Out of the metaproteome-derived data, PD was found to be associated with selected bacterial taxa, and functional classes related with neuronal communication, DNA/RNA metabolism, and alterations in the Major Histocompatibility Complex-I [41].…”
Section: Implications Of Gut Microbiota In Parkinson's Disease (Pd)mentioning
confidence: 99%
“…Following an innovative approach, Flores Saiffe Farías et al performed an in-silico framework to associate metaproteins with the brain proteins expression through ontological labels. Out of the metaproteome-derived data, PD was found to be associated with selected bacterial taxa, and functional classes related with neuronal communication, DNA/RNA metabolism, and alterations in the Major Histocompatibility Complex-I [41].…”
Section: Implications Of Gut Microbiota In Parkinson's Disease (Pd)mentioning
confidence: 99%
“…For example, stimulation of extrasynaptic NMDA receptors can mediate upregulation of the CLCA1 (calcium-activated chloride channel) and activation of p38 (mitogen-activated protein kinase p38) both of which contribute to neuronal death [15][16][17]. In addition to NMDA receptor subcellular location, receptor subunit composition is also crucial in the characterization of the neuronal fate following cerebral ischemia [18].…”
Section: Nmda Receptorsmentioning
confidence: 99%
“…Receptor subunit composition determines receptor permeability and function. They are permeable to sodium and potassium ions and generally not permeable for calcium ion [18]. Their role in neuronal fate following ischemia is not well understood, but there is evidence that their activation can stimulate survival pathways through regulation of the inhibitory neurotransmitter, c-aminobutyric acid (GABA).…”
Section: Nmda Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…An in silico metaproteomic study suggested that the microbiota can impact ion transport, neurotransmitter release, and synapse organization in the basal ganglia, triggering Parkinson's disease. 69 Additionally, the microbiota can regulate the immune system, in particular, major histocompatibility complex 1, and exert epigenetic effects on gene expression, leading to other central nervous system diseases such as depression and autism. A new metaproteomic study investigated the relationship between the metaproteome and major depressive disorder (MDD).…”
Section: Dysbiosis Linked To Major Depressive Disordermentioning
confidence: 99%